Delay in Completion and the Employer's Entitlement for Liquidated Damages under UAE Law and FIDIC Standard form Contracts - KHRAIS, RAMI ISSA (2021)
The construction field is a complicated system that interfaces all stages of engineering, procurement and assembly. Furthermore, all of these activities interface the legal system (eg regulations, liabilities and entitlements) as bound by contract under the law applicable to the project. In this context, the subject of this master’s dissertation is the phenomenon of delayed project completion, the concise meaning of ‘completion’ alongside the completion types to verify the existence of delays and liquidated damage entitlements for the employer based on the construction project delay under UAE law and International Federation of Consulting Engineers (FIDIC) contracts. Construction contracts usually contain clauses and conditions; such as articles for the compensation method to be applied in the case of disputes based on losses or damages caused by a party’s failure to meet the other party’s obligations. The amount of this loss is considered a lump sum and is agreed upon by all parties during the contracting stage, which is ideally prior to the work in question. The aim of such provisions is to financially protect injured parties from damages and losses. This dissertation examines legislation covering the damage liquidation policies of construction contracts and the mechanisms of applying said compensation of liquidated damages under UAE law and the FIDIC. This research also addresses the burden of proof on the injured party in raising a claim for the liquidated damages and the fairness of the applicable UAE laws, especially concerning covering losses not explicitly mentioned in the contract. The author of this work has examined the details of UAE courts and their power to adjust liquidated damages in such cases. To this end, the author provides recommendations to contracting parties to be followed to avoid such losses and to ensure smooth and perhaps unchallenged claims while obtaining appropriate compensation.